PENGARUH KOMPETENSI PROFESIONAL GURU PAK TERHADAP MOTIVASI BELAJAR SISWA KELAS VIII - Eliana Sitohang; Lydia Indriswari; Yuel Sumarno (Bethel Press, 2020)
The Influence of Professional Competence for PAK Teachers on Learning Motivation for Class VIII Students at SMP Imanuel Victori Bekasi Jl. Bojong Nangka IV / 45 Jatirahayu Pondok Melati, East Jakarta. In this thesis the researcher uses the rationale and theories that refer to related literature books, especially books on teacher education and professionalism, and from scientific theories in analyzing data, to determine the sample using the Nonprobability Sampling technique. Nonprobability Sampling is a sampling technique that does not provide equal opportunities/opportunities for every element or member of the population to be sampled. Therefore the population was used as the sample, so the research sample was 35 students who filled out the questionnaire. The results showed that the Effect of PAK Teacher Professional Competence on Student Motivation Class VIII at SMP Imanuel Victori Bekasi Jl. Bojong Nangka IV / 45 Jatirahayu Pondok Melati, East Jakarta, is strong at 37.3% and the remaining 62.7% is determined by other variables not explained by the researcher.